2020
DOI: 10.1001/jamadermatol.2020.1966
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Aspects of a Papulovesicular Eruption in a Patient With COVID-19

Abstract: patients 1 and 2), trichiasis (patients 2 and 4), and excessive tearing (patient 4). Patient 1 had phimosis that was corrected surgically.Discussion | In our experience using etanercept as treatment for patients with SJS-TEN, including in adults, we have made the following noteworthy observations (although these are only anecdotal). First, we found that a response to treatment with etanercept, namely decreased erythema of existing lesions and halting of progression of new lesions, often occurs 24 to 36 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Mahé et al [32] reported on 3 patients with typical COVID-19-associated papulovesicular rash, in which the histological pattern of skin lesions showed prominent acantholysis and dyskeratosis associated with the presence of an unilocular intraepidermal vesicle in a suprabasal location. Based on these histopathological findings, the authors refused the term “varicella-like rash” and proposed a term which was more suitable in their view: “COVID-19-associated acantholytic rash.” Histopathological findings of another case of papulovesicular eruption revealed extensive epidermal necrosis with acantholysis and swelling of keratinocytes, ballooning degeneration of keratinocytes and signs of endotheliitis in the dermal vessels [33]. Acantholysis and ballooned keratinocytes were found also by Fernandez-Nieto et al [31] in 2 patients.…”
Section: Papulovesicular Exanthemmentioning
confidence: 87%
See 1 more Smart Citation
“…Mahé et al [32] reported on 3 patients with typical COVID-19-associated papulovesicular rash, in which the histological pattern of skin lesions showed prominent acantholysis and dyskeratosis associated with the presence of an unilocular intraepidermal vesicle in a suprabasal location. Based on these histopathological findings, the authors refused the term “varicella-like rash” and proposed a term which was more suitable in their view: “COVID-19-associated acantholytic rash.” Histopathological findings of another case of papulovesicular eruption revealed extensive epidermal necrosis with acantholysis and swelling of keratinocytes, ballooning degeneration of keratinocytes and signs of endotheliitis in the dermal vessels [33]. Acantholysis and ballooned keratinocytes were found also by Fernandez-Nieto et al [31] in 2 patients.…”
Section: Papulovesicular Exanthemmentioning
confidence: 87%
“…In our opinion, even if seeking DNA of Herpesviridae family members is ideally advisable, clinical diagnosis may be reliable in most cases, and the role of herpes viruses as mere superinfection in patients with dysfunctional immune response associated with COVID-19 needs to be considered [38]. To our knowledge, SARS-CoV-2 has not been hitherto isolated by means of reverse transcriptase PCR in the vesicle fluid of papulovesicular rash [33, 31].…”
Section: Papulovesicular Exanthemmentioning
confidence: 99%
“…The characteristics of skin lesions in patients with COVID-19, as described recently in case reports or case series, are summarized in the Table 1 [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ,…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Data on SARS-CoV-2 detection in lesional skin are controversial. [1][2][3][4][5][6][7][8] We report a PCR-proven COVID-19 patient with a chilblain-like SARS-CoV-2-positive skin lesion. An 80-year-old woman presented to the emergency department at the end of March 2020.…”
Section: Sars-cov-2 Spike Protein Is Present In Both Endothelial and mentioning
confidence: 93%
“…1 Reports on direct or indirect SARS-CoV-2 investigation in skin lesions of COVID-19 patients are relatively rare yet. [4][5][6][7][8] Santonja et al 5 recently found granular positivity of spike protein in dermal endothelial cells and epithelial cells of eccrine glands of a RT-PCR-negative patient with chilblain-like lesions. Trellu et al 6 and Ahuoach et al 7 performed RT-PCR for SARS-CoV-2 in two COVID-19 patients with skin eruptions.…”
Section: Sars-cov-2 Spike Protein Is Present In Both Endothelial and mentioning
confidence: 99%